PERKEMBANGAN MAJALAH FIKIRAN RA’JAT PADA MASA PERGERAKAN NASIONAL TAHUN 1932-1933 - Ria Mariana; Umi Hartati (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this study was to determine the background and objectives of the publication of the magazine Fikiran Ra'jat 1932-1933, knowing the contents of the Fikiran Ra'jat magazine 1932-1933, knowing the influence of the existence of Fikiran Ra'jat magazine on the Indonesian people during the national movement in the year. 1932-1933, and knowing the end of the publication of the magazine Fikiran Ra'jat in 1932-1933. Methods In this study, researchers used historical methods with heuristic data collection techniques through several stages, namely collection of sources, conducting source criticism both internally and externally, verifying data, and interpreting. Based on the research results, the History of the Press in Indonesia was pioneered by the European Nation, namely Britain. The first time the press was in the form of an official circular or official document printed by the Dutch, for example the result of an agreement. The background for the publication of the Fikiran Ra'jat Magazine was the political situation at that time. The Fikiran Ra'jat magazine is famous for its Popular Political Magazine, the contents of the Fikiran Ra'jat magazine are mostly about political issues that occurred during the movement period. The contents of the magazine talked a lot about capitalism and imperialism committed by the Dutch against the Indonesian people (Marhaen). The influence of the magazine Fikiran Ra'jat on the life of the Indonesian people, namely in the political, economic and social fields.